Consulta de enfermagem à pessoa vivendo com HIV/AIDS : uma proposta de instrumento para coleta de dados - Araujo, Clarissa Eudoxio da Silva de (2021)
Introduction: The introduction of technological advances in the treatment of HIV/AIDS has contributed to an increase in the survival of people living with HIV. However, the change in the profile of the disease to a chronic condition brought several new challenges to be faced, such as the impact of antiretroviral therapy and the development of comorbidities, which can hinder adherence to treatment. In this sense, instrumentalizing nursing care focused on the specific needs of persons living with HIV/AIDS contributes to improving the quality of care provided, and may bring benefits to the professional, to the patients and to the institution. Objectives: To develop and validate the content of an instrument for the nursing consultation with people living with HIV/AIDS, based on Wanda Aguiar Horta's Theory of Basic Human Needs. Methodology: This is a methodological study that was developed in three stages. First stage: a) identification of empirical indicators of basic human needs of the person living with HIV/AIDS through an integrative literature review, and b) construction of the initial instrument of the study containing the empirical indicators according to the levels of Basic Human Needs, as presented by Horta. Second stage: content validation by nurses working in the care of persons living with HIV/AIDS. Third stage: construction of the data collection instrument for the nursing consultation with the person living with HIV/AIDS, including the indexes validated by the nursing judges. Results: 158 empirical indexes were identified and, after the validation of the initial instrument by the judges, 126 indexes reached the weighted average ≥0.80, being 72 (57.14%) of the psychobiological needs, 52 (41.27%) of the psychosocial needs and 2 (1.59%) of the psychospiritual needs. Thus, the final version of the data collection instrument for the nursing consultation with the person living with HIV/AIDS was created, structured according to Wanda Horta's Theory of Basic Human Needs. Product: A data collection instrument for the nursing consultation with the person living with HIV/AIDS. Conclusion: The data collection instrument for the nursing consultation with the person living with HIV/AIDS enables the identification of the altered needs of these patients, according to the levels of need described by Wanda Horta, grounding the nurse's clinical practice and favoring the adequate planning of the nursing assistance. The instrument will be adopted to the clinical practice of nurses working in the reference centre for sexually transmitted infections in the municipality of Vitória